Implementation of total quality management components in Libyan iron & steel company "Lisco" - Safar, Hisham; Bielova, Olena; Бєлова, Олена Ігорівна (Scientific Center of Innovative Researches OÜ, 2021)
Quality is usually considered as a combination of characteristics of an object, which testifies to its ability to satisfy identified needs, the author's proposed definition of the concept of quality management for a company as the system of management, aimed at planning, implementation, improvement and quality control of the company in accordance with the established policy and objectives of the company, with the participation of all its units. Customer satisfaction depends on the fact that the company has an effective quality management system. Thus, an integrated quality management system is created and implemented as a means of ensuring the implementation of specific policies and the achievement of quality objectives set by top management. Therefore, special attention is paid to the formation and documentation of the company's management policy on the quality of products provided to consumers. Manufacturing companies in Libya face difficulties to introduce Total Quality Management system. The original result indicates that lack of skilled labor, employee culture resistance to change, and lack of management commitment and leadership are correlated with a variety of factors that hinder advancement. A lack of benchmarking and employee resistance to change were found to be the top two obstacles. Proper training should be provided to workers to reduce employee resistance and there should be more participation in different stages of implementation. Real problem for the construction sector in Libya is the implementation of quality projects. The main factors influencing the implementation of quality management systems in construction projects are top management commitment, communication, teamwork, employee involvement, and work environment and culture. Following a comprehensive review of several studies on TQM and also considering the importance of critical effecting factors of manufacturing sector in Libya, this study proposed 12 components or factors of TQM for LISCO. A questionnaire made to help finding out the factors and components those affecting implementation of TQM system in the company and identifying correlation between these variables (components). Descriptive statistics and SPSS analysis were employed to indicate the TQM effective components for best implementation which can be applied in order to achieve quality performance.
Keywords: management; quality management; operational management; manufacturing; Total Quality Management (TQM); TQM components; TQM Implementation